Clinical exome sequencing for diagnosing severe cryptogenic liver disease in adults: A case series. (15th February 2022) - Pelusi, Serena; Ronzoni, Luisa; Malvestiti, Francesco; Bianco, Cristiana; Marini, Ilaria; D'Ambrosio, Roberta; Giannotta, Juri Alessandro; Soardo, Giorgio; Maggioni, Marco; Prati, Daniele; Valenti, Luca
Abstract: Liver diseases remain unexplained in up to 30% of adult patients; genetic analysis could help establish the correct diagnosis. In six adult patients with cryptogenic liver disease, we performed whole‐exome sequencing (WES) and evaluated the individual predisposition to progressive fatty liver disease by polygenic risk scores (PRS). In one patient, WES was allowed to diagnose the Hermansky–Pudlak syndrome. In the other two patients, genetic variants in LDLRAP1 / MSH6 and ALDOB genes were identified, contributing to explaining the clinical presentation and disease pathogenesis (50% diagnostic uptake). In the other three patients, rare variants with a high likelihood of disrupting protein function in APOB, ATP7B, ABCB4 and ATP8B1 were identified. One patient who developed hepatocellular carcinoma during the follow‐up had a high PRS value. The study supports the role of WES, combined with risk stratification by PRS and accurate clinical assessment in improving the diagnosis and informed management in patients with cryptogenic liver disease, a positive family history or severe fatty liver not fully accounted for by environmental triggers.